Sonaten, Sonatinen und kleine Stücke für Pianoforte [dritte Abteilung, pt. 2] von Ludwig van Beethoven ; Neue Ausgabe mit Fingersatz von Gustav Damm - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Damm, Gustav, 1830-1904 (editor):::Contributor:::::::::::: (Germany; Leipzig; J. G. Mittler, 2022)
Volume 3, part 2, of the collection of "Sonaten, Sonatinen und kleine Stücke" edited by Gustav Damm (Theodore Steingräber) and published by J. G. Mittler in Leipzig in 1874. This volume includes the piano sonatas opp. 26-111 (except opp. 49/1-2 and 79).